Pengaruh Perceived Organizational Support Terhadap Kinerja Melalui Kepuasan Kerja Karyawan PT. Artha Veda Pekanbaru - Najra Nurani Nasution; Okta Karneli (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine whether perceived organizational support has an effect on performance, to find out whether perceived organizational support has an effect on employee job satisfaction, to determine whether job satisfaction has an effect on performance, and to determine whether perceived organizational support has an effect on performance through employee job satisfaction. The research method used is a quantitative method and uses secondary and primary data. Primary data was obtained from respondents who were collected through a questionnaire. The sample is 74 employees of PT. Artha Veda Pekanbaru from 292 populations by using random sampling technique. The scale of measurement uses a Likert scale. The data analysis includes: Outer Model, Inner Model and Hypothesis Testing. The research data analysis technique used SmartPLS 4. The results showed, (1) there was a significant effect of perceived organizational support on the performance of PT. Artha Veda Pekanbaru, (2) there is a significant effect of perceived organizational support on job satisfaction of employees of PT. Artha Veda, (3) there is a significant effect of job satisfaction on the performance of PT. Artha Veda, (4) there is a significant effect of perceived organizational support on performance through job satisfaction of employees of PT. Artha Veda.